PERANCANGAN MODEL KONSEPTUAL INKUIRI MORAL INTEGRATIF DALAM KONSTRUKSI NILAI PENDIDIKAN AGAMA ISLAM: KONSTRUKSI KONSEPTUAL BERBASIS EPISTEMOLOGI BAYANI–BURHANI - Silmi Kapatan Inda Robby; Kama Abdul Hakam; Mupid Hidayat; Warlim Isya (Universitas Muhammadiyah Bandung, 2025)
Islamic Religious Education (IRE) frequently remains cognitively oriented, limiting students’ moral awareness and capacity for ethical reasoning. Existing moral inquiry models rely largely on value-neutral Western frameworks, creating philosophical misalignment with the normative foundations of Islamic epistemology. This conceptual research employed an Integrative Literature Review to synthesize theories from Social Constructivism, Moral Inquiry (Community of Inquiry), and Islamic epistemology. Literature was critically selected through a structured Critical Content Analysis to identify gaps between rational moral inquiry and the Bayani–Burhani epistemic foundations of IRE. The study proposes a Five-Stage Integrative Moral Inquiry Model that systematically guides learners from moral-dilemma formulation toward value internalization (ma’rifah). Its central innovation is the Integrative Justification Stage, which requires that rational ethical arguments (Burhani) be validated through authoritative scriptural sources (Bayani). This ensures that moral reasoning aligns with Islamic normative certainty while preserving rational autonomy within the inquiry process. The model addresses the theoretical tension between open-ended rational inquiry and religious normative commitments by embedding epistemological integration at the core of instructional design. Its theoretical validity is supported by Vygotsky’s Constructivism and Al-Ghazali’s principles of moral education. This conceptual model provides a comprehensive framework for IRE to cultivate critical thinking, moral sensitivity, and spiritually rooted value construction.